Messenger Ribonucleic Acid of Dormant Spores of Bacillus subtilis - Jeng, Yun-Hua (1974)
Evidence of the presence of messenger ribonucleic acid (mRNA) in dormant spores of Bacillus subtilis has been obtained. The bulk RNA from spores was isolated and labeled in vitro with tritiated dimethyl sulfate. The spore RNA hybridized to 2.4 to 3.2% of the B. subtilis genome. The RNA hybridized to both the complementary heavy and light fractions of deoxyribonucleic acid (DNA). Bulk RNA from log-phase cells competed with virtually all the spore RNA for the heavy DNA fraction and with part of the spore RNA for the light DNA fraction. Bulk RNA from stage IV cells in sporulation also competed with all of the spore RNA for the heavy DNA fraction and with essentially all the spore RNA for the light DNA fraction. These results indicate that dormant spores contain mRNA species present in both log-phase cells and stage IV cells of sporulation. The RNA polymerase in the developing forespore must be able to recognize promotor sites for both log-phase and sporulation genes.